PTU-078 The "getting fit" project in nottingham: a comparison of faecal haemoglobin levels as measured by oc sensor and hm jack in primary care. (17th June 2017) - Chapman, C; Banerjea, A; Ng, O; Rogers, R; Barke, A; Duffin, A; Dale, K; Logan, RF
Abstract : Introduction: NICE guidance (NG12) published in 2015, on indications for urgent referral for possible colorectal cancer (CRC) included the use of faecal occult blood tests (FOB) but did not specify the type of FOB to be used. Quantitative faecal immunochemical tests (FIT) are now available for analysis of occult blood. Recent draft recommendations from NICE propose using a FIT with a 10 µg Hb/g faeces threshold to guide referral in primary care although it is unclear if all analysers perform the same way in a clinical setting. Method: In September 2016 FIT was incorporated into Nottingham's straight to test (STT) pathway. GPs were also given access to FIT for eligible low risk patients (under 60 years without rectal bleeding) using a specific referral form vetted by Nottingham's straight to test pathway team. FIT kits from 2 different manufacturers were posted to patients with instructions for use, along with return packaging. Patients were asked to complete both kits and sample faecal material from the same bowel motion. All returned kits were analysed according to manufacturer's protocols (EIKEN OC-Sensor and Alpha HM Jack) and results expressed in µg Hb/g faeces. Results: So far 90% of GP requested samples have been returned (17/19). The median time to return was 8 days, with time-to-return ranging from 5 to 28 days. Hb values ranged from 0 to 112 µg Hb/g faeces for OC Sensor and 0 to 429 µg Hb/g faeces for HM Jack. Using a cut off of 10 µg/g for OC sensor and 7 µg/g for HM Jack 4/17 (24%) of the GP requested samples would be considered 'positive' in either test, although only 2 of these would have been the same patient. Complete agreement between both tests using a 10 µg/g cut off was seen for only 1 subject. Variation could be due to difference in the assays, or occult blood distribution within faecal samples. Conclusion: Although numbers are small, FITs sent by post following GP requests appear acceptable to subjects to complete and return. Referral on the basis of a single cut off of 10 µg/g would see different patients sent for 2WW referral. Data from these referrals, taken together with the data produced from our 2WW pathway suggests an analyser specific cut off will be needed. Differences in levels of Hb within the same individual bowel motion appear to occur highlighting the importance of repeating tests for individuals whose symptoms persist. Disclosure of Interest: None Declared